2013
DOI: 10.1155/2013/529589
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of Fertility in Azoospermia Rats after Injection of Adipose-Tissue-Derived Mesenchymal Stem Cells: The Sperm Generation

Abstract: The recent reports on the treatment of azoospermia patients, in which spermatozoa could not be traced in their testes, are focused more on the potential use of adult stem cells, like mesenchymal stem cells (MSCs). The aim of this study was to demonstrate the potential use of MSCs derived from adipose tissue in the treatment of azoospermia using rat disease models. After busulfan application, the rats (n = 20) were injected with the GFP+ MSCs into left rete testes. After 12 weeks, the testes with cell injection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
85
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 107 publications
(89 citation statements)
references
References 64 publications
4
85
0
Order By: Relevance
“…As regard to the testicular tissue testosterone, the levels returned to control values with stem cell therapy in gentamicin injected group while estradiol levels returned nearly to control values with stem cell therapy only at the 10 th week of gentamicin injection. These results are in agreement with Cakici et al [47] who reported that treatment of male infertility and testosterone deficiency was possible by adult stem cells. In accordance with our results also, Wu et al [48] reported that MSCs from human bone marrow are able to differentiate into steroidogenic or testicular Leydig cells in vitro.…”
Section: Effect Of Stem Cell Therapy On Serum Testosterone and Testicsupporting
confidence: 93%
“…As regard to the testicular tissue testosterone, the levels returned to control values with stem cell therapy in gentamicin injected group while estradiol levels returned nearly to control values with stem cell therapy only at the 10 th week of gentamicin injection. These results are in agreement with Cakici et al [47] who reported that treatment of male infertility and testosterone deficiency was possible by adult stem cells. In accordance with our results also, Wu et al [48] reported that MSCs from human bone marrow are able to differentiate into steroidogenic or testicular Leydig cells in vitro.…”
Section: Effect Of Stem Cell Therapy On Serum Testosterone and Testicsupporting
confidence: 93%
“…These results are in agreement with Cakici et al (2013) (Cakici et al, 2013), who recorded that MSCs were present in both the external basal partitions and in the internal side of seminiferous tubules. Such observations suggest that MSCs might possess a role in recovering spermatogenesis via two mechanisms: 1) MSC transformation into sperm, or 2) preservation of the spermatogonial cells.…”
Section: El-wakf Et Al (2009) (Elsupporting
confidence: 92%
“…rAT-MSCs were isolated and cultured as described previously (4). Briefly, rats (n=6) were anesthetized by injection of 10 mg/kg xylazine and 75 mg/kg ketamine.…”
Section: Isolation and Culture Of Rat-mscsmentioning
confidence: 99%
“…To confirm the phenotypic characteristics of the isolated cells, undifferentiated MSCs were first subjected to flow cytometric analysis using a FACSCalibur (BD Biosciences, San Jose, CA). The analysis was performed against the following antigens: CD29, CD45, CD54, CD90, and CD106 (BD Biosciences) as described previously (4). The in vitro studies of adipogenic, osteogenic, and neurogenic differentiations were performed according to the methods described previously (4).…”
Section: Characterization Of Rat-mscsmentioning
confidence: 99%
See 1 more Smart Citation